CODE-SWITCHING IN ENGLISH CLASS: A STRATEGY IN BOOSTING LEARNERS’ CONFIDENCE AND ENGAGEMENT - OLIVERA, LARA CELENIA (International Journal of Arts, Sciences and Education, 2021)
Recently, the issue of using the vernacular inside an English class has been a topic of great controversy; hence, this study was conducted to identify the positive effects of code-switching in an English class. Specifically, this aims to determine how this controversial issue in the field of language teaching can boost the learners’ confidence and engagement during class discussions. The data obtained revealed that the use of CS inside an English class bears positive effects on the level of confidence and engagement of the learners. The pedagogical implications of the study can be used and be considered by language teachers to further improve second language acquisition among the learners. Based on the learners’ own experiences and responses, which served as the data used in this study, the use of code-switching has a positive effect on increasing and boosting their confidence and engagement during English classes; consequently, the teacher also plays a great part in boosting the learners’ motivation to participate and engage themselves in discussions. Hence, during the teaching-learning process, teachers should make their best to optimize learners’ emotional factors, lower their affective filters that is, high motivation, low anxiety and this will be possible with the use of code-switching.